Aberrant global DNA methylation in neurodegeneration: ALS and trinucleotide repeat disorders - Hamzeiy, Hamid. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Amyotrophic lateral sclerosis (ALS) is a late onset neurodegenerative disease of the motor neurons, leading to death within two-three years of onset. Extensive studies have thus far helped identify many genetic causes for this devastating disease, but despite such efforts, more than 80% of ALS still remains unexplained. ALS is generally considered to be a polygenic disease, and many different factors may be involved in its pathogenesis, including a combination of rare mutations and environmental factors which could ultimately lead to epigenetic modifications. Here, we investigated ALS from an epigenetic perspective, focusing on 5-methylcytosine (5-mC), a well-characterized epigenetic modification, aiming to conclude disputes between different studies reporting inconsistent results for global 5-mC levels detected in blood samples of sporadic ALS (sALS) patients. The study was further extended to different subtypes of ALS, including familial ALS (fALS), C9orf72 expansion carrier ALS (C9orf72+ ALS) and ATXN2 intermediate expansion ALS along with spinocerebellar ataxia types 1 and 2 (SCA1 and SCA2), Huntington’s disease, Friedreich’s ataxia and myotonic dystrophy type 1. In order to analyze the global 5-mC levels, in DNA isolated from blood, an enzyme-linked immunosorbent assay (ELISA) kit was selected upon testing of commercially available kits. The results showed that increased global 5-mC levels are not exclusive to sALS (p < 0.001 [F(1, 214) = 11.993, p = 0.000645]) and that this can also be observed in different subtypes of fALS. Interestingly, SCA1 (p < 0.01 [F(1, 32) = 8.778), p = 0.00571]) and SCA2 (p < 0.01 [F(1, 56) = 10.784, p = 0.001768]) patients also showed increased levels of global 5-mC when compared to age- and sex-matched healthy controls. Additionally, direct bisulfite sequencing was utilized to investigate the C9orf72 promoter in C9orf72+ ALS patients and healthy controls. Promoter hypermethylation was observed in patients and was moderately correlated (rs = 0.3902, p < 0.05) with the global levels of 5-mC. We also tested several commercial kits for the quantification of 5-hydroxymethylcytosine and could not find a suitable kit for its detection in blood.
Keywords: Amyotrophic lateral sclerosis.